Postharvest Storage, Packaging and Handling of Specialty Crops: A Guide for Florida Small Farm Producers - Jonathan Adam Watson; Danielle Treadwell; Steven A. Sargent; Jeffrey K. Brecht; William Pelletier (EDIS, 2016)
Every year farmers must harvest their crops. This process marks the end of the growing season and carries social significance in communities, but it also creates challenges for producers trying to deliver fresh, high-quality produce to market. Good postharvest practices establish appropriate cold chains that maintain the correct temperatures, humidity, and respiration rates while also ensuring the safety, sanitation, and quality of the fruits. These postharvest practices differ, depending on the size and economic situation of an operation. This 18-page fact sheet provides postharvest storage, packaging, and handling recommendations for small farm specialty crop producers. Written by Jonathan Adam Watson, Danielle Treadwell, Steven A. Sargent, Jeffrey K. Brecht, and William Pelletier, and published by the Horticultural Sciences Department, October 2015.